(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. Assessment of glomerular filtration rate (GFR) is the best index of kidney functions. We aimed to determine the accuracy of El-Minia equation for estimation of GFR in different stages of chronic kidney disease (CKD) in the El-Minia population of CKD patients, in comparison to other proposed equations. Materials and Methods. The study included 320 isotopic GFR measurements by 99m-Tc technetium diethylene triamine pentaacetic acid. Patients were categorized into the five CKD stages based on this measurement, and estimated GFRs based on the El-Minia, Cockroft-Gault, Chronic Kidney Disease Epidemiology Collaboration, Modification of Diet in Renal Disease (MDRD), abbreviated MDRD, Walser, Nankivell, Cockcroft-Gault, and Mayo Clinic equations were validated using the National Kidney Foundation guidelines. Results. The El-Minia Equation showed the best performance in all 5 stages of CKD, except for stage 1, in which the Cockroft-Gault equation showed the best performance (44% within ± 10% error). In addition, the El-Minia equation provided the best accuracy to classify CKD stages, except for stage 4, in which the MDRD gave the best accuracy (82%). Worsening of the accuracy was documented in all the eight equations with more severe stages of kidney disease. These results were not significantly changed when the analyses were restricted to diabetic patients. Conclusions. The El-Minia equation represents a better estimation of GFR in all stages of CKD than other published equations for CKD patients in El-Minia, Egypt. This equation was the best one for classification of CKD in these patients.